Pop culture-inspired programs for tweens, teens, and adults - Alessio, Amy J.; LaMantia, Katie; Vinci, Emily, 1988- (ALA Editions, 2018)
"This book will engage your library's users through toy-centric events that riff on Everything Barbie, Strawberry Shortcake, Cabbage Patch Kids and more; Poodle Totes, Flannel Pillows, Flair Fun, Graffiti Art, and other DIY projects; video screenings such as I Want My MTV, Nostalgia Nickelodeon Night, Cult Movie Fest, and Marvel Madness; programs that incorporate yummy treats like cake pops, Chex mix, Classic Candies by the Decade, and popular microwaveable foods from the 80s; and themed book discussion groups, board game gatherings, trivia contests, and many more fun programs. Everything old is new again in this delightful collection of programs that will have patrons coming back to your library for more"--Provided by publisher.